Regulation of soil ammonia-oxidizing microbial community assembly by alfalfa (Medicago sativa) planting duration in the Loess Plateau - Li, Liangliang; Luo, Zhuzhu; Nian, Lili; Li, Lingling; Niu, Yining; Zhang, Yaoquan; He, Renyuan; Liu, Jiahe (Frontiers in Microbiology, 2025)
To investigate the effects of long-term alfalfa planting on the structure and diversity of soil ammonia-oxidizing microbial communities, this study conducted a field experiment in the semi-arid region of the Loess Plateau. Alfalfa fields planted in 2019 (L2019), 2012 (L2012), and 2003 (L2003) were studied, with farmland corn serving as the control (CK). High-throughput sequencing was used to examine the ammonia-oxidizing microbial communities and their interactions in alfalfa with varying planting durations. The results demonstrated that alfalfa planting significantly increased the levels of total nitrogen, and organic carbon compared to CK. The gene abundance of ammonia-oxidizing archaea (AOA) and ammonia-oxidizing bacteria (AOB) increased with longer alfalfa planting durations. The ecological network analysis showed that at low planting years, species in the AOA community were mainly in a collaborative relationship, while species in the AOB community were mainly in a competitive relationship. This relationship changed at high planting years. Structural equation modeling indicated that planting duration was significantly correlated with Soil water content, total nitrogen, and ammonium nitrogen. Additionally, AOB communities were significantly positively correlated with NH4+-N and negatively correlated with nitrate nitrogen. Ecological null model analysis revealed that the assembly of AOA and AOB communities was primarily governed by stochastic processes, with uncertainty being a key factor in the random assembly process. Furthermore, the β-nearest taxon index (βNTI) of AOB was significantly correlated with Soil water content. This suggests that long-term alfalfa planting forms a stable soil environment, enhancing stochastic processes, which is conducive to maintaining the sustainability and stability of the artificial grassland ecosystem function.